Clinical comorbidity in patients with osteoarthritis: a case-control study of general practice consulters in England and Wales. Issue 4 (12th March 2004) - Kadam, U T; Jordan, K; Croft, P R
Abstract : Objectives: To determine patterns of clinical comorbidity in general practice consulters with OA and compare them with comorbidity in consulters without OA. Methods: A case-control study nested in a one-year prevalence survey of consultations in 60 general practices in England and Wales. Cases were 11 375 subjects aged 50 and over who had consulted with OA during the study year. Controls were 11 780 subjects matched for age and sex who had consulted during the study year, but not for OA. Morbidity outcomes were based on a standard clinical classification system. Results: After adjusting for age, sex, and social class, cases were significantly more likely to have high levels of comorbidity than controls (2.35; 2.16 to 2.55). Significant OA comorbid associations with other musculoskeletal conditions included arthropathies (OR 2.26; 99% CI 1.50 to 3.41), upper limb sprain (2.04; 1.38 to 3.00), synovial and tendon disorders (2.03; 1.54 to 2.68), and other joint disorders (2.00; 1.71 to 2.32). OA non-musculoskeletal associations were with obesity (2.25; 1.73 to 2.92), gastritis (1.98; 1.46 to 2.68), phlebitis (1.80; 1.28 to 2.52), diaphragmatic hernia (1.80; 1.29 to 2.51), ischaemic heart disease (1.73; 1.13 to 2.66) and intestinal diverticula (1.63; 1.20 to 2.23). Conclusions: Comorbidity for OA was extensive, with musculoskeletal as well as non-musculoskeletal conditions. Age, sex, and social class did not explain this comorbidity but propensity to consult may be a part explanation. An important question remains as to whether comorbidity in general practice significantly adds to the disability or further impairs the health of patients with OA.